Phenotypic and genotypic characterization of antimicrobial resistance of Campylobacterisolates from poultry meat in Turkey - Can, HY (Journal of the Hellenic Veterinary Medical Society, 2023)
Phenotypic and genotypic antimicrobial resistances of Campylobacter strains from chicken meat were investigated. A total of 19 isolates (Campylobacter jejuni=6 and Campylobacter coli=13) were identified by multiplex PCR. The C. jejuni and C. coli isolates were tested for resistance to ciprofloxacin, erythromycin, and tetracycline using the disc diffusion method. In addition, all the strains were analyzed for resistance gene tet-O and mutations in the gyrA and 23S rRNA genes by PCR. Overall, a high frequency of resistance was detected against tetracycline (14/19, 73.6%), followed by erythromycin (7/19, 36.8%), and ciprofloxacin (6/19, 31.5%). Two of C. coli isolates (15.3%) were multidrug resistant, whereas none of the C. jejuni isolates were resistant to three antibiotics at the same time. Ten of the 14 Campylobacter strains (71.4%) resistant to tetracycline carried tet-O gene. Mutations in the 23S rRNA and gyrA genes were identified in 57.1% (4/7), 66.6% (4/6) of the isolates resistant to erythromycin and ciprofloxacin, respectively.